KONSUMSI DAN KECERNAAN NUTRIEN PAKAN BASAL RUMPUT RAJA DENGAN TAMBAHAN GLIRICIDIA, KALIANDRA, ATAU DAUN NANGKA PADA KAMBING BLIGON - , RUDY ADRIYANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aimed to determine the consumption and digestibility of king grass and supplemented with gliricidia, calliandra, or jackfruit leaves on bligon goats. The experiment used the 20 heads of female bligon goats approximately 1 year old with an average weight of 16 kg. attle are placed randomly in completely randomized design (CRD) which is divided into four groups (K, T1, T2, and T3), each treatment consisted of 5 of goats. K (100% King grass). T1 (50% king grass and 50% Gliricidia sepium), T2 (50% king grass and 50% Calliandra calothyrsus), and T3 (50% king grass and 50% Artocarpus heterophyllus). Basal feed on the calculation of an average of 4% of body weight in the form of Dry Matter (DM). Variables that were observed during the study was the consumption and digestibility of dry matter (DM), organic matter (OM), crude protein (CP), crude fiber (CF), and ether extract (EE). The results showed that the addition of the basal feed of king grass (T1, T2, and T3) on bligon goats give significant effect (P<0,05) on dry matter intake (DM), organic matter (OM), crude protein (CP), ether extract (EE), but feed treatments T1 and T2 showed no significant effect (P>0,05) on consumption of crude fiber (CF). Nutrient digestibility of feed treatment (T1,T2, and T3) also gave significant effect (P<0,05) against consumption DM, OM, CP, EE, but feed treatments T1 and T2 showed no significant effect (P>0,05) against CF digestibility. Significant effect (P<0,05) was also shown on the daily weight gain (ADG). ADG each successive treatment is K 31.7 g/day, T1 59.7 g/day, T2 58.4 g/day, and T3 66.0 g/day. Based on this study, it can be concluded that the addition of Gliricidia, kaliandra, and jackfruit leaves on basal feed of king grass could increase consumption and digestibility of nutrients, as well as ADG on bligon goats.